2008
DOI: 10.1016/j.ijgo.2008.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cervical mucus aspiration before intrauterine insemination

Abstract: Cervical mucus aspiration before IUI might improve clinical pregnancy rates by yet-to-be-defined mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…When considering cervical mucus aspiration before IUI, Simsek et al found it to be associated with improved pregnancy outcomes (24% in the mucus‐aspiration group versus 9.5% in the non‐aspiration group, P = 0.04). In their randomized trial, Ghasemi et al reported a clinical pregnancy rate of 14.2% among cases of unexplained infertility who underwent mucus removal before insemination ( P = 0.04; OR, 2.199; CI 95%, 0.997–4.85).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When considering cervical mucus aspiration before IUI, Simsek et al found it to be associated with improved pregnancy outcomes (24% in the mucus‐aspiration group versus 9.5% in the non‐aspiration group, P = 0.04). In their randomized trial, Ghasemi et al reported a clinical pregnancy rate of 14.2% among cases of unexplained infertility who underwent mucus removal before insemination ( P = 0.04; OR, 2.199; CI 95%, 0.997–4.85).…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study show that removal of the cervical mucus from the internal and external cervical os before IUI can improve pregnancy outcomes in women with unexplained infertility. The exact mechanism by which cervical mucus removal can enhance pregnancy outcomes is still insufficiently studied, but once this mucus is present, especially if abundant, it may: cause failure of insemination by reducing release of sperm from the catheter; interfere with sperm–oocyte interaction; or push possibly contaminated mucus into the uterine cavity where it may either kill the newly formed embryos or hinder their attachment to the endometrium by stimulating uterine contractions …”
Section: Discussionmentioning
confidence: 99%
“…In Erhan Simsek study in 2008 cervical mucus aspiration before IUI improved outcome of IUI [11]. It should be mentioned the difference between our study with Simsek study was using swab for CM clinging instead of CM aspiration through the catheter.…”
Section: Discussionmentioning
confidence: 68%
“…Tubal flushing has previously proved to be one way of increasing the chance of acheiving pregnancy for couples with increased infertility and early stage of endometriosis 8 . Hydrotubation treatment can be administered in an outpatient clinic and represents a less invasive treatment alternative 9 . The effect of hydrotubation on fertility can be mechanical as well as immunological like inhibited phagocytosis of spermatozoa and by affecting level of peritoneal factors such as cytokines 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It can act by dislodgement of debris in fallopian tubes or by separating the loose adhesion of the tubes. It can also remove thick hostile cervical mucus which may hinder the passage of sperms through the cervix 9 . There may be stimulation of peristalsis by flushing of fluid and dilution of toxic factors such as cytokines in endometriosis 7 .…”
Section: Introductionmentioning
confidence: 99%